QTL effects and epistatic interaction for flowering time and branch number in a soybean mapping population of Japanese×Chinese cultivars - Guang YANG; Hong ZHAI; Hong-yan WU; Xing-zheng ZHANG; Shi-xiang LÜ; Ya-ying WANG; Yu-qiu LI; Bo HU; Lu WANG; Zi-xiang WEN; De-chun WANG; Shao-dong WANG; et al. (Journal of Integrative Agriculture, 2017)
Flowering time and branching type are important agronomic traits related to the adaptability and yield of soybean. Molecular bases for major flowering time or maturity loci, E1 to E4, have been identified. However, more flowering time genes in cultivars with different genetic backgrounds are needed to be mapped and cloned for a better understanding of flowering time regulation in soybean. In this study, we developed a population of Japanese cultivar (Toyomusume)×Chinese cultivar (Suinong 10) to map novel quantitative trait locus (QTL) for flowering time and branch number. A genetic linkage map of a F2 population was constructed using 1 306 polymorphic single nucleotide polymorphism (SNP) markers using Illumina SoySNP8k iSelect BeadChip containing 7 189 (SNPs). Two major QTLs at E1 and E9, and two minor QTLs at a novel locus, qFT2_1 and at E3 region were mapped. Using other sets of F2 populations and their derived progenies, the existence of a novel QTL of qFT2_1 was verified. qBR6_1, the major QTL for branch number was mapped to the proximate to the E1 gene, inferring that E1 gene or neighboring genetic factor is significantly contributing to the branch number.